1988
DOI: 10.1139/z88-346
|View full text |Cite
|
Sign up to set email alerts
|

Comparative gill characteristics of Munida quadrispina (Decapoda, Galatheidae) from different habitat oxygen conditions

Abstract: The allometric (bilogarithmic) relationship between dry gill weight and organic body weight was compared for benthic galatheid crabs (Munida quadrispina Benedict, 1902) from a low-oxygen fjord and from a normal oxygen population. In the M. quadrispina from the low-oxygen fjord, the slope (b) of the allometric function of gill weight versus body weight was 1.00. This b value was significantly higher (ANCOVA, p < 0.01) than the corresponding slope for the same function in M. quadrispina from normoxic areas (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…A study of the decapod Munida quadrispina showed that gill size is developmentally plastic and responds to exposure to chronic hypoxia. Populations of M. quadrispina subjected to chronic severe hypoxia nearly doubled their ratio of gill dry mass to dry body mass compared to counterparts in normoxic waters (Burd, 1988). Plasticity in gill size in response to hypoxia has also been reported for bullfrog Rana catesbeiana larvae (Bond, 1960) and salamander, Salamandra maculosa and Ambystoma jeffersonianum , larvae (Burggren & Mwalukoma, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…A study of the decapod Munida quadrispina showed that gill size is developmentally plastic and responds to exposure to chronic hypoxia. Populations of M. quadrispina subjected to chronic severe hypoxia nearly doubled their ratio of gill dry mass to dry body mass compared to counterparts in normoxic waters (Burd, 1988). Plasticity in gill size in response to hypoxia has also been reported for bullfrog Rana catesbeiana larvae (Bond, 1960) and salamander, Salamandra maculosa and Ambystoma jeffersonianum , larvae (Burggren & Mwalukoma, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Benthic organisms have higher respiratory surface area, with respect to size or per unit mass, in waters with lower oxygen levels (Burd 1988, Lamont & Gage 2000, Jeffreys et al 2012). However, these adaptations to increase O 2 flux can increase the risk of exposure to sulfide.…”
Section: Sulfide and Hypoxia Tolerance In Neoproterozoic Oceansmentioning
confidence: 99%
“…Despite their abundance, slender sole are not commercially important because of their small size (Froese & Pauly, ). Squat lobster is distributed from Alaska to California (Benedict, ) and is physiologically adapted to living in extremely low‐oxygen concentrations (Burd, ). In general, squat lobsters (superfamilies Chirostyloidea and Galatheoidea) are common in low‐oxygen environments (Lovrich & Thiel, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the lower threshold of aerobic energy transfer in metazoan food webs can be determined by the physiological limits of the component species. For example, squat lobsters are well adapted to flourish in low oxygen; they have plastic gill morphologies for enhanced respiration (Burd, ) and low critical oxygen tensions (~0.14 mL L −1 , Burd, ). Also, high densities of squat lobster can occur well below the severe hypoxia threshold (~100 individuals m −2 in <0.2 mL L −1 , Burd & Brinkhurst, ).…”
Section: Discussionmentioning
confidence: 99%